Topography elicits distinct phenotypes and functions in human primary and stem cell derived endothelial cells. (March 2020) - Arora, Seep; Lin, Shiming; Cheung, Christine; Yim, Evelyn K.F.; Toh, Yi-Chin
Abstract: The effective deployment of arterial (AECs), venous (VECs) and stem cell-derived endothelial cells (PSC-ECs) in clinical applications requires understanding of their distinctive phenotypic and functional characteristics, including their responses to microenvironmental cues. Efforts to mimic the in-vivo vascular basement membrane milieu have led to the design and fabrication of nano- and micro-topographical substrates. Although the basement membrane architectures of arteries and veins are different, investigations into the effects of substrate topographies have so far focused on generic EC characteristics. Thus, topographical modulation of arterial- or venous-specific EC phenotype and function remains unknown. Here, we comprehensively evaluated the effects of 16 unique topographies on primary AECs, VECs and human PSC-ECs using a Multi Architectural (MARC) Chip. Gratings and micro-lenses augmented venous-specific phenotypes and depressed arterial functions in VECs; while AECs did not respond consistently to topography. PSC-ECs exhibited phenotypic and functional maturation towards an arterial subtype with increased angiogenic potential, NOTCH1 and Ac-LDL expression on gratings. Specific topographies could elicit different phenotypic and functional changes, despite similar morphological response in different ECs, demonstrating no direct correlation between the two responses.